PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN BIOLOGI KELAS XI-IPA 1 SMA MUHAMMADIYAH 1 PEKANBARU - Hanan Nadya Az Zuhara Hanan Nadya Zuhara; Evi Suryawati Suryawati; Arnentis ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is purpose to know to increase learning creativity and resource of student’s learning by means of the application of project- based learning model to improve the skills of creative thinking and learning outcomes students learning outcomes in learning biology class XI-Science 1 Senior High Scholl Muhammadiyah 1 Pekanbaru second semester grade 2014/2015. Research time is March to May 2015. The subject in the research is students class XI-Science 1 with 23 students. The research instrumen used syllabus, lesson plans, student worksheet and worksheet project. Instrumen data used creative thinking skill assessment sheet, skills assessment, moral assessment and evaluated task. From research result that can know average presentation creative thinking skills of students  that cyclical I is 74.57% or 2.98 (B/good). In cyclical II is 89.5% or 3.59 (A/excellent). Skills project in cyclical I is 85.77% or 3.43 (B+/good). In cyclical II is 91.05% or 3.64 (A-/excellent). Skills product in cyclical I is 81.52% or 3.26 (B+/good). In cyclical II is 87.00% or 3.48(B+/good). Students moral  in cyclical I is 84.22% or 3.36 (B+/good). In cyclical II is 91.80% or 3.67 (A-/excellent ). The absorption of the student in cyclical I is 85.08% or 3.40 (B+/good). In cyclical II is 87.82% or 3.51 (B+/good). The due diligence in cyclical I is 65.21% or 2.60 (B-/good). In cyclical II is 82.60% or 3.30 (B+/good). The application of project- based learning model can improve the skills of creative thinking and learning outcomes students learning outcomes in learning biology class XI-Science 1 Senior High Scholl Muhammadiyah 1 Pekanbaru. Keywords: Project-based learning model, creative thinking skills, learning result.